El cerdo cimarrón (Sus scrofa, Suidae) en la Isla del Coco, Costa Rica: Escarbaduras, alteraciones al suelo y erosión - Sierra, Claudine (2001)
Feral pigs (Sus scrofa) are of the most damaging exotic vertebrates, specially on oceanic island native communities. Feral pigs inhabit Cocos Island since 1793 and there are around 400-500 individuals. In order to quantify the impacts of the feral pigs at Cocos Island, I calculated the effect of the rooting activity and its influence on the natural erosion. During one year I walked, monthly, 15 km on trails estimating rooted area by transect and rooting recurrence. During eight months I compared erosion rates with and without rootings. I estimated the annual rooting rate between 10 and 20 % of the total island surface. The rooted area was the only measured variable which correlated with the soil erosion rate. The erosion rate without rootings was 23.6 kg/ha/year and with rootings was 200.4 kg/ha/year (P < 0.01). The disturbances provoked by the rootings were not scattered homogeneously through the island. The rootings, together with the natural landslides, dominate the soil disturbance pattern at Cocos Island. This study suggests that the presence of feral pigs produces more erosion than the one that would naturally occur without feral pigs at Cocos Island.